EFEKTIVITAS BAKTERI ASAM LAKTAT YANG DIISOLASI DARI SUSU KUDA SUMBA TERHADAP KUALITAS SILASE JERAMI PADI - Annytha Ina Rohi Detha; Frans Umbu Datta; Elisabet Beribe; Nancy D. F. K. Foeh; Nemay Ndaong (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
This study aims to evaluate the ability of lactic acid bacteria isolated from Sumba horse milk as a starter in improving the quality of rice straw silage. Determination of the quality of rice straw silage through organoleptic tests, measurement of percentage of silage damage and silage pH. there are 7 treatments based on silage compositions and lactic acid bacteria. The results showed the presence of golden color in all treatments as the original color, the texture was very soft to soft and not slimy, and the presence of a distinctive silage odor or close to the typical smell of silage in all treatments. The presentation of silage damage to rice straw in the positive control group showed the highest percentage of damage that was equal to 43.58%, while the percentage of damage in the treatment group ranged from 28.57% to 41.02%. The pH results showed the control group had a pH of 3.6 and the P1-P6 group had an average pH ranging from 5.7 to 6.5. The addition of lactic acid bacteria in the manufacture of silage in rice straw provides good quality silage results.